A fast and easy method to obtain pure cultures of Fusarium oxysporum - K. A. Elias (Fungal Genetics Reports, 1997)
Komada’s medium (Komada 1975 Rev. Plant Protec. Res. 8:114-125) was developed as an agar-based selective medium to isolate Fusarium oxysporum from raw soil or infested plant material.